2014
DOI: 10.3389/fneng.2014.00003
|View full text |Cite
|
Sign up to set email alerts
|

Decoding repetitive finger movements with brain activity acquired via non-invasive electroencephalography

Abstract: We investigated how well repetitive finger tapping movements can be decoded from scalp electroencephalography (EEG) signals. A linear decoder with memory was used to infer continuous index finger angular velocities from the low-pass filtered fluctuations of the amplitude of a plurality of EEG signals distributed across the scalp. To evaluate the accuracy of the decoder, the Pearson's correlation coefficient (r) between the observed and predicted trajectories was calculated in a 10-fold cross-validation scheme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 57 publications
(110 reference statements)
9
40
0
Order By: Relevance
“…Indeed, similar resultsthat the useful information in EEG BCI may be encoded by the lowest EEG frequency bandsis also indicated in past studies including such of upper limb movement intentions [74]- [77], studies involving field potential [78]- [81], ECoG [29], [30], [82], and closed-loop studies with implanted intra-cortical electrodes [83]. On the other hand, traditionally motor-imagery EEG BCI have used power modulation in higher frequency bands of EEG signal such as mu (8)(9)(10)(11)(12)(13) and beta (20-30 Hz) rhythms.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, similar resultsthat the useful information in EEG BCI may be encoded by the lowest EEG frequency bandsis also indicated in past studies including such of upper limb movement intentions [74]- [77], studies involving field potential [78]- [81], ECoG [29], [30], [82], and closed-loop studies with implanted intra-cortical electrodes [83]. On the other hand, traditionally motor-imagery EEG BCI have used power modulation in higher frequency bands of EEG signal such as mu (8)(9)(10)(11)(12)(13) and beta (20-30 Hz) rhythms.…”
Section: Discussionsupporting
confidence: 82%
“…Lately, electroencephalography(EEG)-has received considerable attention, due to a number of advantages while data mining and dealing with brain waves. There are tremendous efforts to make use of biomimicry for EEG waves understanding, [2][3][4][5]. In this regard, Yuanfang et al [6], stated they have used two novel classifiers: biomimetic pattern recognition and sparse representation.…”
Section: Biomimetic Engineering For Eeg Applicationsmentioning
confidence: 99%
“…First, 76% (19 of 25) study participants contributed IC's to the R mu component cluster and 64% (18 of 25) study participants contributed IC's to the L mu component cluster with ~ 10% of the residual variance left unexplained by the dipole model. The number of participants that contributed IC's to the R and L mu clusters is consistent with the results of previous studies (Bowers et al, 2013;Gwin & Ferris, 2011;Jenson et al, 2014;Makeig et al, 2004;Moore et al, 2012;Paek et al, 2014). Although the proportion of RV that was unexplained by the dipole model was ~10% in both mu clusters, which is slightly higher than reports from previous studies, these findings are similar to those reported by Jenson and colleagues (2014).…”
Section: Aim 1: Using Ica To Identify Sensorimotor and Muscle Activitysupporting
confidence: 75%